2010
DOI: 10.1111/j.1440-6055.2009.00725.x
|View full text |Cite
|
Sign up to set email alerts
|

Native saltbush (Rhagodia spp.; Chenopodiaceae) as a potential reservoir for agromyzid leafminer parasitoids on horticultural farms

Abstract: Australia has to date been spared the introduction of highly polyphagous invasive pest agromyzid leafminers; however, their arrival and spread should be considered imminent. To develop a pre-emptive control strategy to deal with exotic leafminer outbreaks the first step is to identify Australian leafmining flies, their plant hosts and their parasitoids to gain an understanding of their population dynamics. Native vegetation may be providing resources for beneficial parasitic wasps plus access to alternative ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…However, Z. latilineatum was one of the more abundant parasitoids in south‐eastern Australia, particularly in early autumn (Wood et al . ), and was the species most frequently reared from L. sativae in 2018 and 2019 on Thursday Island, Horn Island and Seisia (EI Pirtle, unpubl. data).…”
Section: Parasitoid Species In Australia Likely To Attack Liriomyza Smentioning
confidence: 99%
See 1 more Smart Citation
“…However, Z. latilineatum was one of the more abundant parasitoids in south‐eastern Australia, particularly in early autumn (Wood et al . ), and was the species most frequently reared from L. sativae in 2018 and 2019 on Thursday Island, Horn Island and Seisia (EI Pirtle, unpubl. data).…”
Section: Parasitoid Species In Australia Likely To Attack Liriomyza Smentioning
confidence: 99%
“…Wood et al . () found high levels of parasitism of Phytoliriomyza praecellens on revegetation plantings of Rhagodia candolleana and Rhagodia parabolica in Virginia, SA. Another unidentified Phytoliriomyza sp.…”
Section: Agromyzid Hosts In Australiamentioning
confidence: 99%
“…There is, however, growing interest in the use of plants that are native to a given area for habitat management. This lack is especially apparent in Australia, as no published information was found on assessing Australian native plant floral resources for benefits such as improving longevity, although a few field studies have shown the benefits of native vegetation as habitat for natural enemies (Stephens et al, 2006;Danne et al, 2010;Wood et al, 2010;Bianchi et al, 2015). Native plants may also be the focus of conservation efforts and will be more valuable than nonnative species in efforts to conserve or restore other native species including vertebrates (Fiedler et al, 2008;Isaacs et al, 2009;Landis et al, 2012), which themselves may serve as biological control agents (G amez-Viru es et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Hemiptarsenus varicornis (Girault) (Hymenoptera: Eulophidae) has been discovered as a major parasitoid of L. trifolii in Japan (Saito et al, 1997;Arakaki and Kinjo, 1998;Ozawa et al, 2001). Hemiptarsenus varicornis is native to Japan, China, Vietnam, Indonesia, Australia and probably to other parts of East and South-East Asia (Konishi, 1998;Rauf et al, 2000;Prijono et al, 2005;Tran et al, 2007;Wood et al, 2010). Hemiptarsenus varicornis is native to Japan, China, Vietnam, Indonesia, Australia and probably to other parts of East and South-East Asia (Konishi, 1998;Rauf et al, 2000;Prijono et al, 2005;Tran et al, 2007;Wood et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Hemiptarsenus varicornis is native to Japan, China, Vietnam, Indonesia, Australia and probably to other parts of East and South-East Asia (Konishi, 1998;Rauf et al, 2000;Prijono et al, 2005;Tran et al, 2007;Wood et al, 2010). Parasitism of L. trifolii by H. varicornis is high in subtropical regions (Arakaki and Kinjo, 1998;Tran et al, 2007;Wood et al, 2010), and this parasitoid shows a high level of thermal tolerance (Hondo et al, 2006), suggesting that H. varicornis is a promising biocontrol agent for controlling leafminers in subtropical regions. Parasitism of L. trifolii by H. varicornis is high in subtropical regions (Arakaki and Kinjo, 1998;Tran et al, 2007;Wood et al, 2010), and this parasitoid shows a high level of thermal tolerance (Hondo et al, 2006), suggesting that H. varicornis is a promising biocontrol agent for controlling leafminers in subtropical regions.…”
Section: Introductionmentioning
confidence: 99%